HMS1 interacts with HMS1I to regulate very‐long‐chain fatty acid biosynthesis and the humidity‐sensitive genic male sterility in rice (Oryza sativa). Issue 5 (16th December 2019) - Chen, Huiqiong; Zhang, Zhiguo; Ni, Erdong; Lin, Jianwen; Peng, Guoqing; Huang, Jilei; Zhu, Liya; Deng, Li; Yang, Fanfan; Luo, Qian; Sun, Wei; Liu, Zhenlan; et al.
Summary: Environment‐sensitive genic male sterility (EGMS) lines are used widely in two‐line hybrid breeding in rice ( Oryza sativa ). At present, photoperiod‐sensitive genic male sterility (PGMS) lines and thermo‐sensitive genic male sterility (TGMS) lines are predominantly used in two‐line hybrid rice, with humidity‐sensitive genic male sterility (HGMS) lines rarely being reported. Here, it is shown that HUMIDITY‐SENSITIVE GENIC MALE STERILITY 1 ( HMS1 ), encoding a β‐ketoacyl‐CoA synthase, plays key roles in the biosynthesis of very‐long‐chain fatty acids (VLCFAs) and HGMS in rice. The hms1 mutant displayed decreased seed setting under low humidity, but normal seed setting under high humidity. HMS1 catalyzed the biosynthesis of the C26 and C28 VLCFAs, contributing to the formation of bacula and tryphine in the pollen wall, which protect the pollen from dehydration. Under low‐humidity conditions, hms1 pollen showed poor adhesion and reduced germination on the stigmas, which could be rescued by increasing humidity. HMS1‐INTERACTING PROTEIN (HMS1I) interacted with HMS1 to coregulate HGMS. Furthermore, both japonica and indica rice varieties with defective HMS1 exhibited HGMS, suggesting that hms1 potentially could be used in hybrid breeding. The results herein reveal the novel mechanism of VLCFA‐mediated pollen wall formation, which protects pollen from low‐humidity stress in rice, and has a potential use in hybrid crop breeding.